Muslim response to war on Iraq - Hosein, Imran Nazar (Kuala Lumpur : Saba Islamic Media)
A talk by Sheikh Imran Hosein, former Foreign Service Officer in the Trinidal and the Tobago Foreign Service on muslim response towards the war in Iraq
Host: Sheikh Imran Hosein
Keywords: Islam; Preaching -- Homiletics